PRODUKTIVITAS DAN KUALITAS GETAH PINUS PEHUTANI KELAS UMUR VII DI KESATUAN PENGELOLAAN HUTAN JEMBER - Dias Evayanti; Febriana Tri Wulandari; Dwi Sukma Rini (Forestry Study Program University Of Mataram, 2019)
The pine resin tapping have done by Perhutani on pine stand at age 11th (age class iii) to 34th (age class vii), whilst pine resin productivity at the end of age period (age class vii) undiscovered. The aims of this study are to determine the productivity of pine resin, the influence of the diameter class to productivity of pine resin, the value of the yield and a lot of quality pine resin resulting in age class VII in Perum Perhutani Regional Division of East Java KPH Jember. The method used in this study was the experimental method by using a completely randomized design in which the treatment used is class D1 = 26-30cm, class D2 = 31-35cm, class D3 = 36-40cm and class D4 = >40cm. Data analysis used is the analysis of variance ANOVA at 5% level and continued with LSD. The results showed that the productivity of Perhutani pine resin KU VII from KPH Jember ranging between 3.17 to 16.04 g/quaree/day, and 8.42 g/quaree/day in average. The diameter classes affect the productivity of pine resin. The resulting yield value at KU VII ranged from 89.6% to 95%, with an overall average recovery rate is 91.4% and the resulting quality of pine resin included in the Super Premium quality.